Developmental regulation of nicotinic synapses on cochlear inner hair cells - Katz, E. (2004)
In the mature cochlea, inner hair cells (IHCs) transduce acoustic signals into receptor potentials, communicating to the brain by synaptic contacts with afferent fibers. Before the onset of hearing, a transient efferent innervation is found on IHCs, mediated by a nicotinic cholinergic receptor that may contain both α9 and α10 subunits. Calcium influx through that receptor activates calcium-dependent (SK2-containing) potassium channels. This inhibitory synapse is thought to disappear after the onset of hearing [after postnatal day 12 (P12)]. We documented this developmental transition using whole-cell recordings from IHCs in apical turns of the rat organ of Corti. Acetylcholine elicited ionic currents in 88-100% of IHCs between P3 and P14, but in only 1 of 11 IHCs at P16-P22. Potassium depolarization of efferent terminals caused IPSCs in 67% of IHCs at P3, in 100% at P7-P9, in 93% at P10-P12, but in only 40% at P13-P14 and in none of the IHCs tested between P16 and P22. Earlier work had shown by in situ hybridization that α9 mRNA is expressed in adult IHCs but that α10 mRNA disappears after the onset of hearing. In the present study, antibodies to α10 and to the associated calcium-dependent (SK2) potassium channel showed a similar developmental loss. The correlated expression of these gene products with functional innervation suggests that Alpha10 and SK2, but not Alpha9, are regulated by synaptic activity. Furthermore, this developmental knock-out of α10, but not α9, supports the hypothesis that functional nicotinic acetylcholine receptors in hair cells are heteromers containing both these subunits.